2020
DOI: 10.24187/ecostat.2019.513.2004
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in Access to Housing: A Test on Urban Areas in Metropolitan France

Abstract: The idea that competitive balance increases the utility of fans, and therefore their spending and the revenue of professional clubs, lies at the heart of sports economics in general and the economics of football in particular. This notion of competitive balance is often invoked to explain the decisions of professional leagues to change the rules of competitions or the distribution of TV rights. However, the empirical literature shows that the relationship between competitive balance and fan demand is far from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, when considering only names with clear signals as being European or not, Moroccan names face higher discrimination by private landlords than Polish names, but not by realtors. This is partly a variation on other research conducted in other European countries, such as Italy (Baldini and Federici, 2011), Sweden (Ahmed and Hammarstedt, 2008), Norway (Andersson et al, 2012), Belgium (Heylen and Van den Broeck, 2016;Verhaeghe and Ghekiere, 2021), Spain (Bosch et al, 2010), France (Le Gallo et al, 2019), and Germany (Auspurg et al, 2017) that systematically found higher discrimination rates against . /fsoc.…”
Section: Discussionmentioning
confidence: 68%
“…However, when considering only names with clear signals as being European or not, Moroccan names face higher discrimination by private landlords than Polish names, but not by realtors. This is partly a variation on other research conducted in other European countries, such as Italy (Baldini and Federici, 2011), Sweden (Ahmed and Hammarstedt, 2008), Norway (Andersson et al, 2012), Belgium (Heylen and Van den Broeck, 2016;Verhaeghe and Ghekiere, 2021), Spain (Bosch et al, 2010), France (Le Gallo et al, 2019), and Germany (Auspurg et al, 2017) that systematically found higher discrimination rates against . /fsoc.…”
Section: Discussionmentioning
confidence: 68%
“…14 By contrast, Le Gallo et al (2020) found that for the 50 largest urban areas in metropolitan France, the levels of discrimination do not differ much between ads from individual landlords or real estate agencies. 15 Following Kahneman & Tversky (1979), some authors ask respondents to indicate what they would themselves do in the situation described in the vignette.…”
Section: Framing: Client-based Discrimination In a Rental Housing Marketmentioning
confidence: 95%
“…In US cities, see Ondrich et al (1999), Choi et al (2005), Zhao et al (2006), Hanson & Hawley (2011), Korver-Glenn (2018), Fang et al (2019), Hellyer (2021), and Chan & Fan (2023). In European cities, see Bosch et al, (2010) for Spain, Gouveia et al (2020) for Portugal, Baldini & Federici (2011) for Italy, Beatty & Sommervoll (2012) for Norway, Carlsson & Eriksson (2014) for Sweden, Auspurg et al (2017) for Germany, Acolin et al (2016), , Le Gallo et al (2020) for France, and for Belgium. In Asia, see Galster et al (2018) for Australia, Liu & Rommel (2023) for China, and Suzuki et al, (2022) for Tokyo.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic minorities are generally found to be treated in an unequal and adverse way on the labor market (e.g., Baert, 2018;Heath & Di Stasio, 2019;Quillian & Midtbøen, 2021;Zschirnt & Ruedin, 2016) and housing market (e.g., Flage, 2018;Quillian et al, 2020). Most European studies find that this adverse treatment is strongest for people of Moroccan or Turkish originwhich is tested by using Muslim namesas compared to people of European descentwhich is tested by using names that are common in the considered ethnic group (e.g., Acolin et al, 2016;Ahmed & Hammarstedt, 2008;Andersson et al, 2012;Baldini & Federici, 2011;Bursell, 2014;Le Gallo et al, 2019;Ramos et al, 2021). However, discrimination towards people of Sub-Sahara African descent is also significantly present (e.g., Verhaeghe & Ghekiere, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%